Sistem Informasi Perusahaan Daerah Air Minum (PDAM) Tanah Laut Berbasis Web Mobile - Novitasari Alivia Agiesta (Journal Information Technology Trends (JITRENDS), 2025)
The Tanah Laut Regional Water Supply Company (PDAM) is engaged in the management and sale of drinking water services in Tanah Laut Regency. Registration is done manually by prospective customers to the customer relations department by coming directly to the Tanah Laut PDAM office, which is then distributed to the planning, planning, engineering, technical, and director departments. Based on the problem, a mobile web-based PDAM Tanah Laut information system is built that can make it easier for customers to register customers and to facilitate officers in distribution. So as to produce the right and efficient data. The information system of Tanah Laut PDAM based on mobile web is built with PHP, HTML, CSS and JavaScript programming languages. And designed using the Entity Relationship Diagram and Data Flow Diagrams.